TEACHING DEAF STUDENTS TO SPORTS AND THE IMPACT OF EXERCISE IN THE PARALYMPIC GAMES - Edan, Mohammed Sachit; Ebady, Mohammed Qasim; abbas, Karrar Jaafar (International Journal of Psychosocial Rehabilitation, 2020)
Talking about "sports for all" is the challenge that the association AMT Concept asbl (Access and Mobility for all) wanted to raise, in collaboration with the Sport sector and Sports infrastructure of the French Community Commission (COCOF) and with support from the Brussels French-speaking Service for People with Disabilities and Works Evening. We hope that this guide will improve the accessibility of sports facilities for people with reduced mobility (PRM)The practice of sport is beneficial for both health and development staff. For people with disabilities, it is a great way to express their potential instead of exposing their limits. Sport appears as an undeniable factor in improving quality of life as much as great tool for recognition and integration into society. The routes of disabled athletes are here to testify to the absolute need to evolve mentalities to make sport accessible to all.